2018
DOI: 10.1007/s00784-018-2632-6
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal tubule penetration of AH Plus, BC Sealer and a novel tricalcium silicate sealer: a confocal laser scanning microscopy study

Abstract: Although no study has confirmed a relationship between the penetration depth of root canal sealers and the prevention of apical periodontitis, dentinal tubule sealer penetration may improve obturation quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 36 publications
13
93
2
Order By: Relevance
“…Despite using human teeth extracted for different reasons (orthodontic or periodontal), the tubular penetration pattern followed the same trend in all teeth. Both for the depth of penetration inside the dentinal tubule and for the percentage of tubular penetration, the apical third showed the lowest results, followed by the middle and coronal thirds; coinciding with other authors [ 17 , 24 , 31 , 36 , 41 , 42 ]. This may be attributed to the differences in dentinal tubule distribution and caliber depending on the root third.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite using human teeth extracted for different reasons (orthodontic or periodontal), the tubular penetration pattern followed the same trend in all teeth. Both for the depth of penetration inside the dentinal tubule and for the percentage of tubular penetration, the apical third showed the lowest results, followed by the middle and coronal thirds; coinciding with other authors [ 17 , 24 , 31 , 36 , 41 , 42 ]. This may be attributed to the differences in dentinal tubule distribution and caliber depending on the root third.…”
Section: Discussionsupporting
confidence: 89%
“…In relation to the results of the present study, ES showed a higher penetration compared to the other sealers although not significantly in all cases. This may be due, partially, to the size of the sealer particles (<1 μm) [ 34 ], which is considerably smaller than that of BR (5–30 μm) [ 35 ] and AHP (1.5–8 μm) [ 36 ]. In addition to its fluidity, this allows the sealer to reach greater depths within the dentinal tubules, with diameters between 2–3 μm [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike scanning electron microscopy, confocal microscopy does not require vacuum or metallization, which is responsible for sample dehydration and the occurrence of technical artifacts 24 . Confocal microscopy has been widely used to observe and evaluate sealer penetration within the dentinal tubules 25 . In the present study, EDTA irrigation with Endovac significantly favored sealer penetration compared with other groups.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, the 1 mm level is chosen to see whether the sealer can seep into apical area between the flutes of instruments and canal walls and can penetrate into the dentine tubules. Several techniques, such as scanning electron microscopy, are available for evaluating the interface between dental material and dentine (Cervino et al, ; Giudice, Cicciù, Cervino, Lizio, & Visco, ; Balguerie, van der Sluis, Vallaeys, Gurgel‐Georgelin, & Diemer, ; Lo Giudice et al, ), light microscopy (Weis, Parashos, & Messer, ), and CLSM (Piai et al, ; El Hachem et al, ). CLSM was used in the present study due its advantages over other detection methods.…”
Section: Discussionmentioning
confidence: 99%